A retrospective observational analysis to identify patient and treatment-related predictors of outcomes in a community mental health programme. Issue 5 (20th May 2015) - Green, Stuart A; Honeybourne, Emmi; Chalkley, Sylvia R; Poots, Alan J; Woodcock, Thomas; Price, Geraint; Bell, Derek; Green, John
Abstract : Objectives: This study aims to identify patient and treatment factors that affect clinical outcomes of community psychological therapy through the development of a predictive model using historic data from 2 services in London. In addition, the study aims to assess the completeness of data collection, explore how treatment outcomes are discriminated using current criteria for classifying recovery, and assess the feasibility and need for undertaking a future larger population analysis. Design: Observational, retrospective discriminant analysis. Setting: 2 London community mental health services that provide psychological therapies for common mental disorders including anxiety and depression. Participants: A total of 7388 patients attended the services between February 2009 and May 2012, of which 4393 (59%) completed therapy, or there was an agreement to end therapy, and were included in the study. Primary and secondary outcome measures: Different combinations of the clinical outcome scores for anxiety Generalised Anxiety Disorder-7 and depression Patient Health Questionnaire-9 were used to construct different treatment outcomes. Results: The predictive models were able to assign a positive or negative clinical outcome to each patient based on 5 independent pre-treatment variables, with an accuracy of 69.4% and 79.3%, respectively: initial severity of anxiety and depression, ethnicity, deprivation and gender. The number of sessions attended/missed were also important factors identified in recovery. Conclusions: Predicting whether patients are likely to have a positive outcome following treatment at entry might allow suitable modification of scheduled treatment, possibly resulting in improvements in outcomes. The model also highlights factors not only associated with poorer outcomes but inextricably linked to prevalence of common mental disorders, emphasising the importance of social determinants not only in poor health but also poor recovery.